2019
DOI: 10.3390/cancers11121940
|View full text |Cite
|
Sign up to set email alerts
|

Switching to Immune Checkpoint Inhibitors upon Response to Targeted Therapy; The Road to Long-Term Survival in Advanced Melanoma Patients with Highly Elevated Serum LDH?

Abstract: The prognosis of patients with advanced melanoma has improved dramatically. However, the clinical outcomes of patients with highly elevated serum lactate dehydrogenase (LDH) remain very poor. The aim of this study was to explore whether patients with normalized LDH after targeted therapy could benefit from subsequent treatment with immune checkpoint inhibitors (ICI). Data from all patients with BRAF-mutant metastatic melanoma with a highly elevated serum LDH at baseline (≥2× upper limit of normal) receiving fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 24 publications
(32 reference statements)
2
22
0
Order By: Relevance
“…The decision tree (CIST) model also showed that ineligible patients with an LDH level of >500 U/L were a prognostic subgroup with poor survival. We previously showed the dismal prognosis in this group of patients and proposed switching to ICI upon response to BRAF(/MEK‐)‐inhibition with LDH normalization as a potential strategy to obtain long‐term survival in these patients 15 . This information supports well‐informed use of systemic therapy in this patient group.…”
Section: Discussionsupporting
confidence: 61%
“…The decision tree (CIST) model also showed that ineligible patients with an LDH level of >500 U/L were a prognostic subgroup with poor survival. We previously showed the dismal prognosis in this group of patients and proposed switching to ICI upon response to BRAF(/MEK‐)‐inhibition with LDH normalization as a potential strategy to obtain long‐term survival in these patients 15 . This information supports well‐informed use of systemic therapy in this patient group.…”
Section: Discussionsupporting
confidence: 61%
“…Interestingly, also response rates to anti-PD1 are lower in patients with stage IV M1c melanoma compared with lower stages, 30 in patients with higher tumour load 29 and LDH ≥2 × ULN. 31 As we and others have recently shown a correlation between ICI response and toxicity, 32 33 one may hypothesise that immunological responses in these patients are less strong, which might be due to the increased immunosuppressive tumour microenvironment in large volume disease. 34 It is unlikely that the observed association between stage and severe irAEs is explained by immortal time bias, as we adjusted for follow-up time.…”
Section: Discussionmentioning
confidence: 87%
“…These results from registries can then be confirmed by randomized controlled trials. An example of supporting evidence from DMTR data on advanced melanoma patients treated with first-line targeted therapy with high LDH showed subsequent immunotherapy could lead to long-term survival if normalization of LDH was reached [ 22 ]. This information is easily obtained with the use of a registry including real-world practices.…”
Section: Discussionmentioning
confidence: 99%